PENGARUH TERAPI MUSIK KELOMPOK TERHADAP TINGKAT KESEPIAN LANJUT USIA DI PANTI SOSIAL TRESNA WERDHA YOGYAKARTA UNIT BUDHI LUHUR KASONGAN BANTUL - , LAILIA NURAINI, Sri Warsini,S.Kep.,Ns.,M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The process of aging causes physical, mental and social changes in the elderly that may affect psychological condition especially in those living at social institution. Elderly people living at social institution are at risk for being lonely. Group music therapy can help minimize loneliness. Objective: The study aimed to identify effect of group music therapy to loneliness of the elderly at PSTW Yogyakarta Unit of Budhi Luhur. Method: The study was a quasi experiment with one group pretest â posttest design carried out at PSTW Yogyakarta Unit of Budhi Luhur. Research instrument used UCLA Loneliness Version 3. Samples were taken through total sampling, comprising 31 elderly. Data analysis used McNemar. Results: Before intervention with group music therapy most of the elderly were lonely (54.8%). After the intervention within 3 weeks there was effect to loneliness of the elderly at PSTW Yogyakarta Unit of Budhi Luhur as indicated from score of McNemar test at significance 0.000 (<0.05). Conclusion: There was effect of group music therapy to loneliness of the elderly at PSTW Yogyakarta of Budhi Luhur.